Desafios e possibilidades para a implementação do novo ensino médio em escolas públicas da região de Santa Maria/RS - Much, Liane Nair (2021)
This work was developed based on studies and reflections made within the Grupo de Estudos, Pesquisa e Intervenções, Inovação Educacional, Práticas Educativas e Formação de Professores (INOVAEDUC). It was created due to concerns referring to the necessity of implementation of the Novo Ensino Médio (New Secondary School, NEM), meeting the current norms and legal orientations on the subject. Thus, an objective was set: “to understand the movement made by Public Schools in the process of implementing the Novo Ensino Médio”. We understand that this work makes itself relevant as we can contribute on the establishment of elements and parameters that may be useful for the schools to participate in an effective and critic manner in the process of implementing NEM. Information was collected/built with the contributions of 23 teachers and 8 pedagogical coordinators of 5 pilot-schools belonging to the 8th Coordenadoria Regional de Educação (CRE) of the Rio Grande do Sul Rede Escolar Pública Estadual (REPE). We used the following practices for the collection/construction of information: 1) interviews with teachers and pedagogical coordinators of pilot-schools; 2) observation of meetings arranged by the 8th CRE with the management and pedagogical teams of the pilot-schools; 3) the use of online questionnaires with the teachers of those schools. The Information was organized and treated with the methodological subsidy of the Grounded Theory. This methodology follows the epistemological school of “Symbolic Interactionism”. It enables theorizations based on the analysis and interpretation of information collected/built by means of the observation of the relations between subjects in their daily lives. The conducted study made it possible to relate the movements made by the pilot-schools to 3 categories of factors: (1) Time: a) little time to study and to appropriate the propositions contained in the legal norms; b) requests made by SEDUC/RS with reduced time limits for their compliance; c) reduced time for the application of an objective questionnaire, received from SEDUC/RS, for the students and the school community, to map their formative interests; d) difficulty on arranging collective meetings for the study and construction of the Propostas de Flexibilização Curricular (PFC, Curricular Flexibilization Proposals); (2) Financial Resources: a) constraints on financial resources destined to the acquisition of material for the development of planned PFCs in schools; b) lack of financial resources to hire professionals for the training of teachers of the schools; (3) Effective work conditions: a) increase of workload for teachers and pedagogical coordinators, who besides addressing usual/typical demands of the school term, also need to appropriate the propositions of NEM, in addition to planning and developing actions solicited by SEDUC/RS; b) maintenance of the already ordinary situation of the exercise of the “teaching profession” in RAPE/RS in which teachers are obliged to work in two or more schools to complete their hiring working hours; c) teachers hired in 2020 were designated to work in pilot-schools and to take on new curricular components that constitute the Educational Programme without previously knowing the propositions of NEM; d) non-observation of a teacher‟s profile to work with the new curricular components of the curriculum‟s diversified part.